Illustration of the emerging capabilities of SARAL/AltiKa in the coastal zone using a multi-platform approach. Issue 1 (1st January 2015) - Troupin, Charles; Pascual, Ananda; Valladeau, Guillaume; Pujol, Isabelle; Lana, Arancha; Heslop, Emma; Ruiz, Simón; Torner, Marc; Picot, Nicolas; Tintoré, Joaquín
Highlights: Glider data were acquired along a SARAL/AltiKa track in August 2013 in the Ibiza Channel. Satellite altimetry, HF radar and glider data are interpolated and filtered to compute the cross-track velocity. All the platforms showed the existence of a 25–30 km width coastal jet with velocities larger than 20 cm/s. Filtered 40 Hz data provided geostrophic current about 10 km from the coast. Abstract: Satellite altimetry measurements from SARAL-AltiKa are analysed in the coastal ocean using the results of the G-AltiKa mission (1–5 August 2013), which combined altimeter, HF radar and glider data coincident with the satellite track, south-west of Ibiza Island, in the Western Mediterranean Sea. The absolute dynamic topography, computed from 1 Hz and 40 Hz altimetry data, and the dynamic height, computed from glider temperature and salinity, both exhibited a weak signal with amplitudes of order 2 cm. The resulting geostrophic and HF radar velocities along the track depicted a north-westward coastal current with a maximal velocity larger than 20 cm s −1 . This demonstrates that the AltiKa altimeter is able to resolve SLA signals of more than 2 cm, and gradients in those signals over several tens of kilometres. After filtering, the 40 Hz data depicted a signal consistent with the other platforms, up to a distance of order 10 km from the coast.